Analisis Yuridis Normatif atas Kekuatan Hukum Nasabah Pinjaman Online dalam Perspektif Undang-Undang Perlindungan Konsumen - Lavina Celestyn Putri Amarufy; Arrijalu Khaira (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid development of digital financial technology, particularly peer-to-peer (P2P) online lending services, has significantly expanded public access to financial resources while simultaneously generating complex legal problems for consumers. Issues such as misuse of personal data, excessive interest rates, non-transparent contractual clauses, and intimidative debt collection practices continue to occur, especially within illegal online lending platforms. Regulatory data indicate persistent violations of consumer protection norms and personal data regulations, despite the existence of statutory frameworks governing fintech activities in Indonesia. Online lending relationships create binding legal obligations between creditors and debtors, positioning consumers in a vulnerable situation due to standard-form contracts and information asymmetry. Normative legal analysis demonstrates that the dissemination of personal data without consent constitutes a violation of consumer protection law, personal data protection law, and general principles of civil liability. Existing regulations provide both preventive and repressive legal protection through transparency obligations, supervisory mechanisms, and sanctions; however, enforcement remains fragmented across institutions. Legal certainty and effective consumer protection require stronger coordination among regulatory authorities, clearer limitations on data access, and stricter accountability for online lending providers. Strengthening the implementation of consumer protection principles is essential to ensure fairness, security, and legal balance within digital financial transactions.